Molecular detection of foot and mouth disease virus serotype A in goats (Capra hircus) (Asian Journal of Medical and Biological Research, 2022)
Foot and mouth disease (FMD) is a highly contagious, transboundary, and re-emerging viral disease that mostly affects cloven-hoofed animals specially cattle, goats, swine, sheep, etc. resulting in significant economic losses. Despite regular vaccination, outbreaks of the disease have become a yearly occurrence across the country. RT-PCR was used to determine the prevalence and molecular detection of serotype A of FMDV in clinically affected goats in Goat research farm, BLRI, Savar, Dhaka, Bangladesh during August 2018. A total of 9 samples were taken from 1 to 2 years old Black Bengal goats suspected to have FMD. FMDV was detected in 55.56% (5/9) of the suspected samples using RT-PCR. The serotype of positive samples was also determined using gsRT-PCR. However, FMDV serotype A was prevalent in 100% (5) positive samples. Additionally, considering the age, the prevalence of confirmed FMD outbreak was 40% (2), 40% (2), and 20% (1) at the age of 1, 1.5 and 2 years, respectively. It was found that young goats are more susceptible to FMDV than adults. However, it can be concluded that suspected goats were infected with FMDV serotype A and trivalent FMD vaccine is suggested for prevention and control of FMD outbreak.Asian J. Med. Biol. Res. 2022, 8 (1), 30-36